A case of reactive lymphoid hyperplasia of the liver in a patient with autoimmune hepatitis - Kanno, Hiroki (Surg Case Rep, 2020)
BACKGROUND: Reactive lymphoid hyperplasia (RLH) of the liver is a benign disorder. It is usually observed in the skin, orbit, thyroid, lung, breast, or gastrointestinal tract, but rarely in the liver. Since the first report of RLH of the liver in 1981, only 75 cases have been described in the past literature. Herein, we report a case of RLH of the liver in a patient with autoimmune hepatitis (AIH), which was misdiagnosed as hepatocellular carcinoma (HCC) preoperatively and resected laparoscopically. CASE PRESENTATION: A 43-year-old Japanese woman with autoimmune hepatitis was followed up for 5 years. During her medical checkup, a hypoechoic nodule in segment 6 of the liver was detected. The nodule had been gradually increasing in size for 4 years. Abdominal ultrasound (US) revealed a round, hypoechoic nodule, 12 mm in diameter. Contrast-enhanced computed tomography (CT) demonstrated that the nodule was slightly enhanced in the arterial dominant phase, followed by perinodular enhancement in the portal and late phases. A magnetic resonance imaging (MRI) scan showed low signal intensity on the T1-weighted image (T1WI) and slightly high signal intensity on the T2-weighted image (T2WI). The findings of the Gd-EOB-DTPA-enhanced MRI were similar to those of contrast-enhanced CT. Tumor markers were all within the normal range. The preoperative diagnosis was HCC and a laparoscopic right posterior sectionectomy was performed. Pathological examination revealed that the nodular lesion was infiltrated by small lymphocytes and plasma cells, and germinal centers were present. Immunohistochemistry was positive for B cell and T cell markers, indicating polyclonality. The final diagnosis was RLH of the liver. CONCLUSIONS: The pathogenesis of RLH of the liver remains unknown, and a definitive diagnosis based on imaging findings is extremely difficult. If a small, solitary nodule is found in female patients with AIH, the possibility of RLH of the liver should be considered.